A double blind, multicentre, placebo controlled trial of lornoxicam in patients with osteoarthritis of the hip and knee. Issue 2 (February 1992) - Berry, H; Bird, H A; Black, C; Blake, D R; Freeman, A M; Golding, D N; Hamilton, E B; Jayson, M I; Kidd, B; Kohn, H
Abstract : Lornoxicam is a new non-steroidal anti-inflammatory agent (NSAID) with a similar pharmacological profile to other oxicams and a potency 10 times greater than piroxicam. A multicentre, randomised, double blind, parallel group study was undertaken to compare the efficacy and tolerance of four weeks' treatment with lornoxicam (6 mg once daily, 4 mg twice daily, and 6 mg twice daily) and placebo in patients with osteoarthritis of the hip or knee. A dose related efficacy of lornoxicam was shown by the numbers of patients in each treatment group who withdrew from the trial owing to inadequate symptom relief (12/40 (30%) receiving placebo, 6/40 (15) receiving lornoxicam 6 mg daily, 4/40 (10%) receiving lornoxicam 8 mg daily, and none receiving lornoxicam 12 mg daily). This effect was confirmed by pain relief scores, which were significantly better than placebo during treatment with lornoxicam 8 mg and 12 mg daily, the effect of 12 mg daily being significantly superior to that of 8 mg daily. Similar results were obtained from functional status scores. Mean functional index (Lequesne) scores were significantly greater than placebo only at a daily dose of 12 mg lornoxicam. Lornoxicam was generally well tolerated, though some gastrointestinal side effects were seen as has been reported with other NSAIDs. Laboratory investigations showed no evidence of drug toxicity.